Flexural fatigue strength prediction of hybrid fibre-reinforced self-compacting concrete. Issue 3 (5th June 2019) - Bawa, Shailja; Singh, S. P.
Abstract : Mathematical models were developed for predicting the flexural fatigue strength of hybrid fibre-reinforced self-compacting concrete based on fatigue test results. Steel and polypropylene fibres were used at 1% total mix volume in various proportions. About 250 flexural fatigue tests and 90 static flexural tests were carried out. Fatigue-life data obtained was analysed to determine the relationship between stress level, number of cycles to failure and probability of failure. It was found the relationship can be represented reasonably well graphically by a family of curves. The experimental coefficients of the fatigue equations were calculated from the fatigue test data to obtain the analytical curves. The 2 million cycle fatigue strength of the concrete mixes was also calculated from the curves.